2018
DOI: 10.1111/famp.12397
|View full text |Cite
|
Sign up to set email alerts
|

Unequally into “Us”: Characteristics of Individuals in Asymmetrically Committed Relationships

Abstract: This study examined characteristics of individuals that are associated with being in asymmetrically committed relationships (ACRs), defined as romantic relationships in which there was a substantial difference in the commitment levels of the partners. These ACRs were studied in a national sample of unmarried, opposite‐sex romantic relationships (N = 315 couples). Perceiving oneself as having more potential alternative partners was associated with increased odds of being the less committed partner in an ACR com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…This suggests that it is highly likely that when couples experience sexuality that includes strong messages and motives for demonstrating emotional connection and caring, it is more likely to be indicative of harmonious sexual passion and satisfaction with many aspects of their relationship and lives. This is yet additional evidence for the importance of helping emerging adults and couples of all ages understand the power of sexuality to significantly enhance life if it is experienced and nurtured in the context of caring relationships (Olmstead et al, 2013; Sprecher et al, 2018; Stanley et al, 2019; Woloski‐Wruble et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that it is highly likely that when couples experience sexuality that includes strong messages and motives for demonstrating emotional connection and caring, it is more likely to be indicative of harmonious sexual passion and satisfaction with many aspects of their relationship and lives. This is yet additional evidence for the importance of helping emerging adults and couples of all ages understand the power of sexuality to significantly enhance life if it is experienced and nurtured in the context of caring relationships (Olmstead et al, 2013; Sprecher et al, 2018; Stanley et al, 2019; Woloski‐Wruble et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although wives in the second class reported improvements in marital satisfaction, their mean levels never surpassed those of the wives in the Relatively satisfied class. Therefore, for wives, these improvements in marital satisfaction may not outweigh available alternatives, making dissolution a desirable option (Stanley et al, 2019). External circumstances may also partially explain why this group demonstrated both improvements in satisfaction and more instability.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study participants who reported more than 100 sexual partners were removed as outliers (N ϭ 9). Several studies have reported mean number of sexual partners in a similar age range to the current sample including means of 7.05 from Liu et al (2015) and means of 6.31 (Stanley et al, 2018). The mean for the Stanley et al study was likely lower than average for lifetime sexual partners because the mean age of the sample was approximately 26, and the question asked about the number or previous sexual partners so participants were not counting their current partner.…”
Section: Methodsmentioning
confidence: 73%